A putative siderophore receptor of Gallibacterium anatis 12656-12 under Fur control also binds hemoglobin - Chantes-Guerra, Alberto; Maldonado-Puga, Samantha; Rojas-Ruiz, Norma; Rea-Hernandez, Ismael; Montes-Garcia, Fernando J.; Trujillo-Ruiz, Hector; Yañez-Aguilar, Ivan E.; Vazquez-Cruz, Candelario; Sanchez-Alonso, Patricia; Negrete-Abascal, Erasmo (Frontiers in Microbiology, 2022)
Pasteurellaceae family members obtain iron directly from host proteins or through siderophore-dependent mechanisms. Although Gallibacterum anatis expresses different virulence factors, its response to growth under iron restriction is unknown. G. anatis cultured in the presence of 2,2´-dipyridyl, up-expressed an approximately 65 kDa protein and repressed the expression of a 70 kDa protein. MALDI-TOF analysis of those proteins indicated homology with CirA (65 kDa), a protein involved in iron-siderophore acquisition in Mannheimia succinoproducens and a TonB-dependent receptor (70 kDa protein), a protein that binds chicken hemoglobin; however, G. anatis siderophore production was not detected by chromo azurol S (CAS)-BHI agar determination. This putative G. anatis siderophore receptor is under Fur control, but not the hemoglobin binding protein, as observed in G. anatis 12656-12 fur mutant (Ω fur 126.13) grown in the presence or not of 2,2´-dipyridyl. The addition of FeCl3 to the culture medium diminished the growth and biofilm production in approximately 30% and 35%, respectively, in the wild-type strain, but the growth of Ω fur 126.13 strain was not affected and biofilm production increased in 35%. G. anatis Ω fur 126.13 presented lower virulence when it was inoculated to 35- day-old chickens in comparison to the wild-type strain. The induction of more than one iron uptake mechanism could benefit pathogenic microorganisms such as Gallibacterium.